Estudios previos sobre la contribución de líquenes epifíticos a la producción de robledales - Müller A.; Schmitz M.F.; Bermúdez de Castro F. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
The nitrogen fixation (ARA) of specimens of Lobaria pulmonaria growing on Quercus pyrenaica trunks in a mixed wood of beech and oak trees in Montejo de la Sierra (Madrid) is determined. The ARA was analysed monthly for a whole year and incubations were made in situ. L. pulmonaria ARA fluctuates throughout the year and shows two maxima in July and October and two minima in May-June and in August-September . The rate of acetylene reduction and the lichen covering indicate estimable nitrogen inputs.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)